Fairness and groups (Research on managing groups and teams, 2010)
Concerns about justice and fairness are ubiquitous within and between communities, social groups, organizations and states. People are concerned with the fairness of how decisions are made, how outcomes are allocated between and within groups, and how they are treated by authorities. This volume introduces cutting-edge justice theorizing and research at the intersection of justice and groups. Contributors to this volume explore topics such as (a) how group members come to have a shared understanding of the level of fairness within their group (i.e., justice climate), (b) how social emotions influence justice judgments, (c) the relationships between trust, respect, fairness, and group-serving behavior, (d) resource allocation, (e) reactions to injustice, (f) appropriate ways to restore justice following transgressions, and (g) perceptions of and remedies for intergroup inequality. The Fairness and Groups volume in the Research on Managing Groups and Teams series will be of interest to students and scholars in psychology, sociology, law and organizational behavior